Antiprogramed cell death‐1 therapy with microspheres for metastatic liver tumors. Issue 6 (24th June 2019) - Kamimura, Hiroteru; Takeda, Nobutaka; Owaki, Takashi; Mizusawa, Takeshi; Iwasawa, Takahiro; Ikarashi, Satoshi; Hashimoto, Satoru; Takamura, Masaaki; Terai, Shuji
Abstract : Anti‐programmed cell death‐1 therapy with microspheres is an effective treatment for metastatic liver tumors.